ANALISIS HUKUM TERHADAP PENOLAKAN SUAMI MENGUCAPKAN IKRAR TALAK DALAM PERKARA PERCERAIAN - Soleh, Yudi Prihartanto (LITIGASI, 2022)
A husband who does not want to divorce may apply to the Religious Courts with the intention to delay the divorce by not declaring the pledge of divorce even though the case is final and binding. If the wife who files for divorce and the case has been decided, automatically the husband and wife are divorced. In case the divorce is filed at the same time, either one cannot file any lawsuit. When the husband does not exercise his right to make a divorce pledge, the wife then can only file a "Divorce Lawsuit" when the case filed by her husband is completed. This hinders the wife to file a divorce that may lead to unclear domestic situation. This study uses a normative juridical method with statutory and analytical approach through multidisciplinary approach, namely from aspects of Marriage Law, Religious Court Law, and KHI. The results showed that by filing a lawsuit in reconvention by the wife, if the husband does not declare the pledge after the decision is final, the divorce can still occur. Thus, the husband cannot impede the process of divorce that can harm the wife. Keywords: Husband's Rejection; Pledge of Divorce; Divorce Case.